2004
DOI: 10.1038/sj.ijo.0802761
|View full text |Cite
|
Sign up to set email alerts
|

Time trends (1993–1997) and seasonal variation in body mass index and waist circumference in the Netherlands

Abstract: OBJECTIVE:To compare the time trend and seasonal variation in body mass index (BMI) and waist circumference. DESIGN: Continuous monitoring health survey carried out between 1 June 1993 and 31 May 1997. SUBJECTS: A total of 8186 men and 9638 women aged 20-59 y from three towns in the Netherlands. MEASUREMENTS: BMI and waist circumference. Obesity was defined as BMI Z30 kg/m 2 , abdominal obesity as waist circumference Z102 cm for men and Z88 cm for women. RESULTS: Levels of BMI and waist circumference increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
78
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 30 publications
11
78
1
1
Order By: Relevance
“…[1][2][3][4] Overweight and obesity have an enormous public health impact. For instance, they are linked to an increased risk of type 2 diabetes mellitus, coronary heart disease, stroke, hypertension, gallbladder disease, some forms of cancer, sleep apnoea, and osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Overweight and obesity have an enormous public health impact. For instance, they are linked to an increased risk of type 2 diabetes mellitus, coronary heart disease, stroke, hypertension, gallbladder disease, some forms of cancer, sleep apnoea, and osteoarthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies from various populations have reported increasing body mass index (BMI) 1 and increasing waist circumference (WC) [2][3][4] during the past decades. Moreover, it seems that WC indicating abdominal obesity is increasing even more rapidly than BMI, [5][6][7] and increasing waistlines or abdominal obesity are observed not only among the obese but also among normal weight subjects.…”
Section: Introductionmentioning
confidence: 99%
“…20 However, little is known about socio-economic characteristics of population groups with increasing waistlines, but overall, there seems to be a greater increase in WC in women. 4,6,7 One study reported that there appears to be more consistent increase in WC with deprivation for both sexes, 5 whereas another showed the greatest increase in waistline among most highly educated women. 3 Data on socio-economic characteristics of those with abdominal obesity are thus limited and results are usually presented separately for BMI and WC.…”
Section: Introductionmentioning
confidence: 99%
“…Its broad dissemination is due to its capacity to express the energy reserves of individuals, ease to obtain, applicability, low correlation with height, and good correlation with body fat measures 6 . As people differ in relation to body composition and location of fat (android or gynecoid patterns), the relation between BMI and morbidity risk may be affected, considering that the main complications of obesity are associated to greater accumulation of abdominal fat, regardless of body weight 7 . Approximately 20% to 30% of the prevalence of hypertension may be due to overweight or obesity 8 .…”
Section: Introductionmentioning
confidence: 99%